Development of broadband optical swtiches for DWDM networks based on photonics MEMS - Dowd, Philip (2008)
In this work, novel Silicon-based MEMS actuator structures are presented, together with a study on the feasibility of using III-V compound semiconductor materials for the fabrication of MEMS devices.